PP-BST3-x implant as well as preparation method and application thereof
By constructing oxygen vacant BST3-x nanoparticles on the surface of the implant and fixing them to the PEKK@pDA scaffold to form a PP-BST3-x implant, the problems of low ROS efficiency and difficulty in bone regeneration of existing materials are solved, and stronger bacterial killing and bone regeneration effects are achieved.
Patent Information
- Application Number
- CN202411664818.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Existing materials have low ROS efficiency when treating implant infection, difficult to separate electron holes, and difficult to regenerate bone tissue around the implant after bacterial infection.
The PP-BST3-x implant was formed by constructing oxygen vacancies on the surface of strontium ion-doped barium titanate and fixed to the surface of the PEKK@pDA scaffold to improve ROS generation efficiency and bone regeneration capacity.
It improves the efficiency of ROS production, enhances the bacterial killing effect, and regulates Sr release, inhibits osteoclast differentiation and promotes bone regeneration and healing.
Smart Images

Figure CN119633175A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medical materials, and specifically relates to a PP-BST 3-x Implant and preparation method and application thereof. Background Art
[0002] The main cause of infection caused by implants is the adhesion and colonization of bacteria on their surfaces, which in turn forms a biofilm. After bacterial infection, it is difficult for bone tissue around the implant to regenerate. Once a biofilm forms on the surface of the implant, it will eventually lead to implant failure due to persistent inflammation and necrosis of surrounding tissues. Since the microorganisms in the biofilm can resist the host's immune attack and have low sensitivity to antibiotics, the removal of the biofilm is particularly challenging in clinical practice.
[0003] Currently, surgical removal of infected implants is still considered the standard of care, but it significantly prolongs the patient's hospital stay and greatly increases medical costs. In order to circumvent the inevitable obstacles of surgical removal, various implant surface modification strategies have been developed to combat bacterial infections. Implant surface modification is the antibacterial modification of the implant surface to reduce bacterial adhesion and inhibit plaque biofilm formation, thereby preventing early postoperative infection. Although this strategy has achieved remarkable success in antibacterial treatment, the antibacterial coatings currently set on the implant surface are mostly traditional antibacterial agents. The relatively long sterilization time and potential bacterial resistance of traditional antibacterial agents have largely hindered their widespread application in clinical practice. In addition, the current implant surface antibacterial coatings still have defects such as structural stability, controllability, and poor timeliness.
[0004] Recently, sonodynamic therapy (SDT) has received widespread attention in the treatment of implant infection due to its advantages such as resistance to bacteria, minimally invasive, deep tissue penetration and immediate therapeutic effect. However, the sonosensitizers currently used in SDT are insufficient to kill bacteria in clinical settings. Existing materials have low efficiency in generating ROS and difficulty in separating electrons and holes. In addition, existing defect engineering only focuses on the generation of ROS, but does not pay attention to the fact that the bacterial infection environment induces osteoclast activity, thereby inhibiting local bone regeneration and inducing implant loosening. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a PP-BST 3-x The invention discloses an implant and a preparation method and application thereof, so as to solve the technical problems of low ROS generation efficiency and low bone regeneration efficiency of existing materials.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a PP-BST 3-x The method for preparing an implant comprises the following steps: S1. Dissolve the titanium source in an organic solvent, then add alkali solution until no sediment is formed to obtain a titanium-containing suspension. The addition of alkali solution will promote the hydrolysis reaction of the titanium source to generate Ti(OH)4 precipitation; dissolve the barium source and strontium source in water, then add the mixed solution to the titanium-containing suspension, react at 170-190°C and 1-5MPa for 46-50h, then wash, and place the washed product at 70-90°C to dry for 22-26h to obtain BST nanoparticles, and finally place the BST nanoparticles in a reducing atmosphere and react at 450-550°C for 10-14h to obtain BST 3-x Nanoparticles; the molar ratio of Ti, Ba and Sr elements in the titanium source, barium source and strontium source is 0.5-1.5:2-4:0.1-0.5; S2, dissolving dopamine (DA) in a buffer solution, and then completely immersing the PEKK scaffold in the dopamine solution for 22-26 hours to allow dopamine to form a uniform polydopamine (pDA) coating on the surface of the PEKK scaffold through an oxidative polymerization reaction, and then washing with water to remove unreacted dopamine monomers and other residues to obtain a PEKK@pDA scaffold (PP); S3. BST 3-x (Ba 0.9 Sr 0.1 TiO 3-x ) nanoparticles were uniformly dispersed in water, and then the PEKK@pDA scaffold was placed on BST 3-x Soak in the suspension for 10-14 hours to allow BST 3-x The nanoparticles were fixed to the surface of the PP scaffold by physical adsorption or chemical bonding, and finally dried at 70-90 °C for 10-14 h to obtain PP-BST. 3-x Implant.
[0007] On the basis of the above technical solution, the present invention can also be improved as follows: Furthermore, the titanium source is Ti(C4H9O)4, Ti[OCH(CH3)2]4 or TiCl4, the barium source is Ba(OH)2˖8H2O, Ba(NO3)2 or BaCO3, and the strontium source is Sr(NO3)2, SrCl2 or SrCO3.
[0008] Furthermore, the organic solvent is ethanol.
[0009] Furthermore, the alkali solution is aqueous ammonia (NH3·H2O), sodium bicarbonate (NaHCO3) or ammonium hydroxide (NH4OH).
[0010] Furthermore, the washing liquid used for washing is at least one of acetic acid, ethanol and deionized water.
[0011] Furthermore, the reducing atmosphere is a mixture of H2 and Ar in a volume ratio of 90-97:3-10.
[0012] Furthermore, the buffer is Tris-HCl buffer, PBS buffer or sodium bicarbonate buffer.
[0013] Furthermore, the concentration of the dopamine solution is 2-4 mg / mL, and the pH value is 8-9.
[0014] Further, BST 3-x The concentration of the suspension was 2-4 mg / mL.
[0015] The present invention also discloses PP-BST prepared by the above preparation method. 3-x Implant.
[0016] The present invention also discloses PP-BST 3-x Application of implants in the preparation of osteogenic materials.
[0017] The beneficial effects of the present invention are: 1. Aiming at the problems of low ROS generation efficiency and difficult electron-hole separation of existing materials, the present invention constructs oxygen vacancies (BST) on the surface of strontium ion-doped barium titanate. 3-x ), the presence of oxygen vacancies makes it easier for electrons and holes to separate, thereby accelerating the reaction of electrons with surrounding substances, increasing the efficiency of ROS production and making the bacterial killing effect stronger.
[0018] 2. To address the problem of difficulty in regenerating bone tissue around implants after bacterial infection, the PP-BST prepared by the present invention 3-x On the one hand, the implant can polarize macrophages through potential to inhibit inflammation; on the other hand, it can regulate Sr release through ultrasound, thereby inhibiting osteoclast differentiation in an infected environment and achieving dual-path osteogenesis. 3-x The implant can inhibit bacteria while improving the high osteoclast environment caused by the bacterial microenvironment, promoting bone regeneration, accelerating bone healing ability, and reducing patient recovery time. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 For BST 3-x TEM images of Figure 2 PEKK@pDA scaffold (PP) and PP-BST 3-x SEM comparison of implants; Figure 3 PEKK@pDA scaffold (PP) and PP-BST 3-x Comparison of the compression Young's modulus of the implants; Figure 4PEKK@pDA scaffold (PP) and PP-BST 3-x Comparison of contact angle data between implant and water; Figure 5 The ability of different components of Sr to produce ROS; Figure 6 PP-BST 3-x Ability to produce ROS (·OH); Figure 7 PP-BST 3-x Produces singlet oxygen (1O 2 ) ability; Figure 8 To compare the bacterial communities of different materials in plate experiments; Fig. 9 Live and dead cell staining diagrams for different materials; Fig.10 The staining diagrams are for M1 and M2 macrophages; Fig.11 This is the trap staining result; Fig.12 This is the staining result of the osteogenic marker RUNX2. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
[0021] Example 1 A PP-BST 3-x The method for preparing an implant comprises the following steps: S1. Dissolve 4 mL of Ti[OCH(CH3)2]4 in 10 mL of ethanol and stir for 30 min, then add sodium bicarbonate until no sediment is formed (Ti(OH)4 precipitation) to obtain a titanium-containing suspension; then transfer the titanium-containing suspension to a Teflon-lined autoclave, dissolve 10 g of Ba(NO3)2 and 8 g of SrCl2 in 20 mL of water at 50°C, stir for 10 min, add the mixed solution to the titanium-containing suspension, react at 170°C and 5 MPa for 50 h, then wash with acetic acid, ethanol and deionized water in sequence, dry the washed product at 90°C for 22 h, and obtain BST nanoparticles; finally, place the BST nanoparticles in a reducing atmosphere (H2:Ar=90:10, v:v) and react at 450°C for 14 h to obtain BST 3-x Nanoparticles; S2, dissolving dopamine (DA) in sodium bicarbonate buffer, then completely immersing the PEKK scaffold in the dopamine solution (concentration of 2 mg / mL, pH 8) and stirring for 22 hours, and then washing with water to obtain a PEKK@pDA scaffold; S3. BST 3-x (Ba 0.9 Sr 0.1 TiO 3-x ) nanoparticles were ultrasonically dispersed in water, and then the PEKK@pDA scaffold was placed on BST 3-x The suspension (concentration of 4 mg / mL) was allowed to stand and soak for 10 h, and finally dried at 90 °C for 10 h to obtain PP-BST. 3-x Implant.
[0022] Example 2 A PP-BST 3-x The method for preparing an implant comprises the following steps: S1. Dissolve 3 mL of TiCl4 in 10 mL of ethanol and stir for 30 min, then add ammonium hydroxide until no sediment is formed (Ti(OH)4 precipitation) to obtain a titanium-containing suspension; then transfer the titanium-containing suspension to a Teflon-lined autoclave, dissolve 9 g of BaCO3 and 0.6 g of SrCO3 in 20 mL of water at 50 °C, stir for 10 min, add the mixture to the titanium-containing suspension, react at 190 °C and 1 MPa for 46 h, then wash with acetic acid, ethanol and deionized water in sequence, dry the washings at 70 °C for 26 h, and finally place the BST nanoparticles in a reducing atmosphere (H2:Ar=97:3, v:v) and react at 550 °C for 10 h to obtain BST 3-x Nanoparticles; S2, dissolving dopamine (DA) in PBS buffer, then completely immersing the PEKK scaffold in the dopamine solution (concentration of 4 mg / mL, pH 9) and stirring for 26 hours, and then washing with water to obtain a PEKK@pDA scaffold; S3. BST 3-x (Ba 0.9 Sr 0.1 TiO 3-x ) nanoparticles were ultrasonically dispersed in water, and then the PEKK@pDA scaffold was placed on BST 3-x The suspension (concentration of 2 mg / mL) was allowed to stand and soak for 14 h, and finally dried at 70 °C for 14 h to obtain PP-BST. 3-x Implant.
[0023] Example 3 A PP-BST 3-x The method for preparing an implant comprises the following steps: S1. Dissolve 3.41 mL of Ti(C4H9O)4 in 10 mL of ethanol and stir for 30 min, then add ammonia water until no sediment is formed (Ti(OH)4 precipitation) to obtain a titanium-containing suspension; then transfer the titanium-containing suspension to a Teflon-lined autoclave, dissolve 9.45 g of Ba(OH)2˖8H2O and 0.7 g of Sr(NO3)2 in 20 mL of water at 50°C, stir for 10 min, add the mixed solution to the titanium-containing suspension, react at 180°C and 3 MPa for 48 h, then wash with acetic acid, ethanol and deionized water in sequence, dry the washed product at 80°C for 24 h, and finally place the BST nanoparticles in a reducing atmosphere (H2:Ar=95:5, v:v) and react at 500°C for 12 h to obtain BST 3-x Nanoparticles, the TEM image is as follows Figure 1 As shown, the formation of oxygen vacancies is also shown; S2, dissolving dopamine (DA) in Tris-HCl buffer, then completely immersing the PEKK scaffold in the dopamine solution (concentration of 3 mg / mL, pH value of 8.5) and stirring for 24 hours, and then washing with water to obtain the PEKK@pDA scaffold (PP); S3. BST 3-x (Ba 0.9 Sr 0.1 TiO 3-x ) nanoparticles were ultrasonically dispersed in water, and then the PEKK@pDA scaffold was placed on BST 3-x The suspension (concentration: 3 mg / mL) was allowed to stand and soak for 12 h, and finally dried at 80 °C for 12 h to obtain PP-BST. 3-x Implant.
[0024] PEKK@pDA scaffold (PP) and PP-BST 3-x SEM images of implants Figure 2 As shown in the figure, it can be seen that the PP porous implant was successfully prepared and the BST 3-x It is ellipsoidal and evenly distributed on the PP surface.
[0025] Example 4 The difference between this embodiment and embodiment 3 is that the amount of Sr(NO3)2 added is adjusted to 0.32 g (5%), and the remaining components and preparation steps are the same as those in embodiment 3 to obtain PP-BST 3-x Implant.
[0026] Example 5 The difference between this embodiment and embodiment 3 is that the amount of Sr(NO3)2 added is adjusted to 0.64 g (10%), and the remaining components and preparation steps are the same as those in embodiment 3 to obtain PP-BST 3-x Implant.
[0027] Example 6 The difference between this embodiment and embodiment 3 is that the amount of Sr(NO3)2 added is adjusted to 0.96 g (15%), and the remaining components and preparation steps are the same as those in embodiment 3 to obtain PP-BST 3-x Implant.
[0028] Comparative Example The difference between this comparative example and Example 3 is that Sr(NO3)2 is omitted, and the remaining components and preparation steps are the same as those in Example 3 to obtain a PP-BT implant.
[0029] The PP-BST used in the following experiments 3-x The implant is PP-BST prepared in Example 3 3-x Implant Experimental Example 1 Mechanical Properties Verification of PP-BST by universal mechanical testing 3-x Mechanical properties of implants, test methods refer to ISO 10993 standard. Figure 3 As shown, PP-BST 3-x The Young's modulus of the implant is 248Mpa, which is lower than that of bone, causing less wear on the bone and more conducive to long-term use.
[0030] PP-BST verified by testing 3-xThe contact of the implant with water is tested by cleaning the surface of the material and then drying it to ensure that there is no contaminant or grease on the surface. Use pure water drops on the surface of the material, 3-5 drops of water per sample to ensure the repeatability of the test, and use a contact angle meter to capture the angle formed by the water drop on the surface. The results are as follows: Figure 4 As shown in the figure, compared with the PP bracket, the BST 3-x The scaffold of the material has good contact with water, which is conducive to bone growth into the prosthesis.
[0031] Experimental Example 2 ROS production capability test The DPBF degradation experiment was conducted to investigate the effect of different Sr doping amounts (Examples 4-6) on the amount of ROS generated by surface oxygen vacancies. The specific steps were as follows: DPBF was dissolved in ethanol to prepare a 100 μM DPBF solution, and the material to be tested was dissolved or dispersed in the ethanol solution to ensure uniform distribution; the DPBF solution and the sample solution were mixed in a certain proportion to ensure that the final concentration of DPBF was 100 μM, and the mixed solution was sonicated for 10 minutes using an ultrasonic device (power 1W / cm²), and finally the absorbance change of DPBF at 410 nm was measured using a UV-Vis spectrophotometer, the absorbance change over time was recorded, and the ratio to the initial value was calculated. The results are shown in Figure 2. Figure 5 As shown, even when the doping amount of Sr(NO3)2 is 10%, PP-BST 3-x The production of ROS by the implants remained unaffected.
[0032] To evaluate the ·OH production, the control group (H2O), PP-BT, and PP-BST 3-x The sample was mixed with a solution containing MB and stimulated by US (1 MHz, 1.0 W / cm 2 , 50% duty cycle), and recorded the absorption changes of MB at 664nm before and after US stimulation. Figure 6 As shown in the figure, it can be seen that PP-BST 3-x The lowest MB fluorescence intensity indicates that MB is degraded. 3-x The ability to produce OH is the strongest.
[0033] The control group, PP-BT, and PP-BST 3-x The sample was mixed with a solution containing SOSG, and the results were as follows Figure 7 As shown, singlet oxygen (1O 2 ) exists, PP-BST 3-x The fluorescence intensity of the group increased, indicating that PP-BST 3-x It produces the most ROS, providing an important basis for sterilization. Figure 6 and Figure 7The black line in the figure represents the control group, the red line represents the PP-BT group, and the blue line represents the PP-BST group. 3-x Group.
[0034] Experimental Example 3 Antibacterial Performance Test The coated plate method was used to evaluate the PP-BST under different US irradiation conditions. 3-x The bactericidal effect on Staphylococcus aureus (ATCC25923) is as follows: PP-BST 3-x Implants were exposed to bacterial suspensions (2 × 10 7 CFU / mL) for 6 h, and the experimental group was subjected to 1W / cm 2 The cells were irradiated with US for 9 minutes, while the control group was not irradiated with US. The cells were cultured on agar plates at 37°C for 18 hours, and the colony forming units (cfu) were quantified. Figure 8 shown.
[0035] For further verification, the bacteria were cultured on different scaffolds for 5 days and then subjected to live / dead staining assay using the live / dead BacLight activity kit. Fig. 9 As shown, PP-BST 3-x There was less green fluorescence (live bacteria) than in the control group, indicating that PP-BST 3-x The implant has good antibacterial ability in the simulated in vivo environment.
[0036] Experimental Example 4 Osteogenesis Performance Detection Evaluation of PP-BST by macrophage (M1, M2) staining 3-x Promote the polarization of M2 macrophages, such as Fig.10 As shown, red is M1 and green is M2; compared with the control group, PP-BST 3-x Having more M2 macrophages can have a better inhibitory effect on inflammation and help improve the inflammatory state of the microenvironment.
[0037] Assessment of PP-BST using trap staining 3-x The ability to inhibit osteoclast differentiation was evaluated by co-culturing different implants and bacterial suspensions with RAW 264.7 cells to evaluate their inhibitory effects on osteoclast formation, and osteoclast formation was induced with bacterial suspensions. For F-actin ring staining, cells were then stained with Actin-Tracker Green to visualize the F-actin ring, and the nuclei were labeled with DAPI, and the stained cells were observed under a fluorescence microscope. Fig.11 As shown in the figure, the smaller the ring is, the stronger the ability to inhibit osteoclasts is. 3-x It has a stronger ability to inhibit osteoclast differentiation.
[0038] Detection of PP-BST using osteogenic related markers 3-x To evaluate osteogenic capacity, MC3T3-E1 cells were seeded into each well of a 12-well plate. After reaching 70% confluence, the α-MEM medium was replaced with 10 mM β-glycerophosphate, 50 µg mL -1 Ascorbic acid and 10nM dexamethasone (both from Sigma) were used to induce osteogenesis in osteoinduction medium, which was renewed every 3 days along with the materials. For immunofluorescence analysis of RUNX2, each group of cells was treated with a specific primary antibody: anti-RUNX2, and then treated with a secondary antibody Alexa Fluor 594 (1:50 00, Invitrogen). FITC-labeled phalloidin was used for cytoskeletal staining, and DAPI was used for nuclear staining to affect the microscopic image acquisition and compare the osteogenic properties. The results are shown in Fig.12 As shown in the figure, the more gold the stronger the bone formation ability. It can be seen that the BSTx group with Sr is better than the BT group without Sr. 3-x It can inhibit osteoclasts, indicating that PP-BST 3-x Has stronger bone-forming properties.
Claims
1. A PP-BST 3-x The method for preparing an implant is characterized in that: The following steps are involved: S1. Dissolve a titanium source in an organic solvent, then add an alkali solution until no more sediment is formed to obtain a titanium-containing suspension; dissolve a barium source and a strontium source in water, then add the mixed solution to the titanium-containing suspension, react at 170-190°C and 1-5MPa for 46-50h, then wash, and dry the washed product at 70-90°C for 22-26h to obtain BST nanoparticles, and finally place the BST nanoparticles in a reducing atmosphere and react at 450-550°C for 10-14h to obtain BST 3-x Nanoparticles; the molar ratio of Ti, Ba and Sr elements in the titanium source, barium source and strontium source is 0.5-1.5:2-4:0.1-0.5; S2, dissolving dopamine in a buffer solution, then immersing the PEKK scaffold in the dopamine solution for 22-26 hours, and then washing to obtain a PEKK@pDA scaffold; S3. BST 3-x The nanoparticles were dispersed in water and the PEKK@pDA scaffold was then placed on BST 3-x Soak in the suspension for 10-14 hours, and finally dry at 70-90°C for 10-14 hours to obtain PP-BST 3-x Implant.
2. The PP-BST according to claim 1 3-x The method for preparing an implant is characterized in that: The titanium source is Ti(C4H9O)4, Ti[OCH(CH3)2]4 or TiCl4, the barium source is Ba(OH)2˖8H2O, Ba(NO3)2 or BaCO3, and the strontium source is Sr(NO3)2, SrCl2 or SrCO3.
3. The PP-BST according to claim 1 3-x The method for preparing an implant is characterized in that: The organic solvent is ethanol.
4. The PP-BST according to claim 1 3-x The method for preparing an implant is characterized in that: The alkali solution is aqueous ammonia, sodium bicarbonate or ammonium hydroxide.
5. The PP-BST according to claim 1 3-x The method for preparing an implant is characterized in that: The washing liquid used for washing is at least one of acetic acid, ethanol and deionized water.
6. The PP-BST according to claim 1 3-x The method for preparing an implant is characterized in that: The reducing atmosphere is a mixture of H2 and Ar in a volume ratio of 90-97:3-10.
7. The PP-BST according to claim 1 3-x The method for preparing an implant is characterized in that: The buffer is Tris-HCl buffer, PBS buffer or sodium bicarbonate buffer.
8. The PP-BST according to claim 1 3-x The method for preparing an implant is characterized in that: The BST 3-x The concentration of the suspension was 2-4 mg / mL.
9. A PP-BST3-x implant, characterized in that: Using the PP-BST described in any one of claims 1 to 8 3-x The implant is prepared by a method for preparing the implant.
10. The PP-BST according to claim 9 3-x Application of implants in the preparation of osteogenic materials.
Citation Information
Patent Citations
3D printing PEKK loaded special knot making system for treating infectious bone defect
CN117339008A
Preparation method and application of ultrasonic activated piezoelectric heterojunction antibacterial coating
CN118059306A
Preparation method of light-triggered pyroelectric nano material
CN118557744A
Composite multifunctional coating with electric response characteristic and preparation and application thereof
CN118846257A
Biocompatible Titanium Alloys
US20070191944A1